Integrasi Materi Entrepreneurship dalam Pengembangan Modul Ajar Bahasa Inggris - Ahmad Syaifuddin (Faculty of Economics and Islamic Business, Sunan Drajat University, Lamongan, 2026)
Implementing a Deep Learning approach in education requires teachers to design instructional modules that foster meaningful, mindful, and enjoyable learning experiences. This mentoring program was conducted with English teachers at SMP Maarif Ammukhtar Brumbun, involving four teachers who were members of the English Subject Teacher Forum. The results demonstrate that, through a systematic mentoring process, the teachers were able to grasp the structure of instructional modules and produce modules that integrated principles of mindful, meaningful, and enjoyable learning, alongside higher-order thinking activities, contextual learning, and reflective assessment. This support proved effective in enhancing the teachers' pedagogical competence in designing contextual and meaningful learning experiences